Rainforest Alliance Sustainable Agriculture Standard: Applicable for Smallholders Farms - Rainforest Alliance (2018)
In January 2018, the Rainforest Alliance merged with UTZ. We joined forces because we know that together we can have a greater impact and be a better partner to the many stakeholders we work with. With this new sustainable agriculture standard, we intend to harmonize the existing standards of the Rainforest Alliance and UTZ, learn from past experiences, but most importantly bring innovation and new insight into certification and agricultural sustainability. Our new sustainable agriculture standard is designed to maximize positive social, environmental, and economic impact, while offering farmers an enhanced framework to improve their livelihoods and protecting the landscapes where they live and work. For this first draft of the standard, a full public consultation is organized from December 2018 to February 2019 to gather feedback and improve this document. This sustainable agriculture standard forms the heart of the Rainforest Alliance’s new certification strategy. In addition to the content of the standard, a larger system of assurance, chain of custody, and monitoring and evaluation will support its implementation. Finally, at the widest level, advocacy and landscape-level interventions support the transformation of sustainable supply chains.